EXISTENCE OF LOCAL LEGAL PRODUCT NUANCED OF SHARI’AH IN INDONESIA - Patra, Rommy (Faculty of Law, Universitas Sebelas Maret, 2017)
The existence of local legal product nuanced of shari'a in Indonesia is rampant in the reform era. The establishment of local legal product that nuanced of shari'a is effort to formalize shari'ah Islam in the life of the nation. But its existence has caused controversy because of have nature of sectarian and vulnerable to violation of human rights such as discriminatory and restrict civil liberties. Therefore, necessary for the structuring of local legal product that nuanced of shari'a, if necessary until to cancel it in order to improve the quality of implementation of local autonomy in Indonesia.